Influence of Class Action Learning Model on The Knowledge, Attitude, and Behavior of Higher-Class Students of State Elementary School 01 Cilandak Timur, South Jakarta - Pudentiana Rr. R. E.; Siti Nurbayani Tauchid (Global Writing Academica Researching and Publishing, 2022)
This study aims to determine the effect of the classroom action learning model on dental health on the knowledge, attitudes, and behavior of upper-class students at Primary School 01 Cilandak Timur, South Jakarta. This study aims to increase students’ knowledge criteria by applying an action learning model for class V Elementary School in Cilandak State Elementary School. The subjects of this study were 32 class V students as the intervention class and class V Elementary School Borobudur as the control class. The method used was Classroom Action Research. This study used a pre and post-test design with a control group. The pre-test and post-test control group designs involve two classes: the experimental and control classes. Before being given treatment, both classes did a pre-test to get the initial cognitive abilities of the fifth graders. Then the two classes were offered the treatment to the experimental class, namely learning by applying good and correct brushing techniques, while the control class was not given any treatment. After learning, a post-test was conducted to determine the cognitive abilities of the experimental class and control class respondents. In this study, the sample used is part of the population, which is 10%. The sample calculation is 0,1 X 300, that is, 30 people in the intervention class and 30 in the control class with different schools. The results of the study can be concluded that the Classroom Action Learning Model in terms of the teacher’s ability to manage the class is said to be effective because the total percentage of good and very good assessments is more than the percentage of poor and quite good assessments, namely: 92% > 8%, Classroom Action Learning Model is reviewed of student activities in learning is said to be effective because the number of percentages of good and very good assessments is more than the number of percentages of poor and good enough assessments, namely: 75% > 25%, Class Action Learning Model in terms of student responses to learning is said to be effective because the number of assessment percentages good and very good more than the total percentage of assessments are not good and quite good, namely: 85% > 15%, Class Action Learning Model in terms of student learning outcomes after learning is said to be effective because the total percentage of assessments understands and understands more than the total percentage appraiser Ian understands well and quite understands, namely: 85% > 15%.